Associating of mother's health literacy with sunlight protective behaviors of teenage children: application of social cognitive theory. Issue 5 (3rd September 2019) - Peyman, Nooshin; Tavakoly Sany, Seyedeh Belin; Nasehnezhad, Mahnaz; Doosti, Hassan; Chesneau, Christophe; Ferns, Gordon
ABSTRACT: The relative contributions of health literacy to promote health-related behaviors and characteristics of social cognition are still equivocal, and relevant information is limited. We aimed to examine the effect of the mother's health literacy level on their teenage children's sun protective behaviors based on social cognitive theory. This was a cross-sectional study of 202 women who had children between 12 and 18 year-old and they live in Sabzevar, Iran. The Test of Functional Health Literacy in adults (TOFHLA) questionnaire and sun protective behavior questionnaire based on structures of the social cognitive theory were used to collect data. Multiple statistical tests (correlation and the regression analysis) were analyses to examine whether the health literacy level of mothers associated with sun protective behaviors of their children. The results showed health literacy level of mother was positively significantly (p < 0.01) correlated with all constructs of social cognitive theory and teens' performance to avoid sunlight (r = 0.242, P < 0.01). Likewise, the self-efficacy showed the strongest correlation with a health literacy level of the mother (r = 0.360, p < 0.01), and with the performance of the teenagers (r = 0.282, p < 0.01). Linear regression showed that all constructs of social cognitive theory and health literacy level of mothers predicted 34.9% of teenage children's sunlight protective behaviors. Health literacy level of mother and constructs from social cognitive theory are significantly supported determinants of sun protective behaviors and could be considered in developing and designing educational interventions program to facilitate a healthy active lifestyle.